Optimization of Laser Cutting Parameters on 700MC Steel Using Grey Relational Analysis - Jaemsang, Orajit; Kaweegitbundit, Parinya; Mookam, Niwat (International Journal of Engineering and Technology, 2018)
This paper presents an investigation of the optimization of laser cutting parameters on 700MC steel. The cutting parameters investigated in this study are focused on Laser power, cutting speed, and gas pressure. Full factorial design (3k) is employed as the random run of the experimental. Grey relational analysis is used to determine the optimization of these parameters. The experimental results show that the optimal cutting condition for laser power, cutting speed and gas pressure is 2600W, 1500 mm/min and 0.06 bars, respectively. In addition, the experimental validation provided the surface roughness and kerf width is 3.870 Î¼m and 0.696 mm respectively.Â Â